Evaluation of the Reliability of Lifting Granes Metal Structures - Kruzhnova, S.Yu.; Fursina, H.D. (Control systems & computers, 2021)
The need to search for additional methods to reduce the accident rate and to improve the safety of the crane fleet is due to the statistics of injuries and accidents at lifting structures, which rank the third after injuries and accidents in the coal and mining industries. A method for assessing the remaining life-circle, which facilitates predicting the loss of strength of a metal structure as a result of fatigue and corrosion damages considered. After analyzing the results of calculating the structure persistence, a decision is made on its further operation. If the results of calculating Q (t),with the consideration of the change in σ-1D in terms of the coefficient of variation, exceed the value of the 25 years durability, then it is inappropriate to calculate its persistence Мета – зменшити суб’єктивний фактор при прийнятті рішень про можливість подальшої експлуатації крана при черговому обстеженні. Результати. Для визначення коефіцієнтів регресії було розглянуто стан 11 вантажопідйомних кранів і результати їх подальшої експлуатації протягом останніх 10 років. Розрахунковий ресурс задавався в частках від нормативного терміну до першого обстеження (10…20 років). Отримано лінійне рівняння для прогнозу ресурсу, в якому всі коефіцієнти значущі, а коефіцієнт множинної кореляції 0,966 є достатньо великим.